The Impact of p53 and Ki67 Expression in Endometrial Cancer and its Effect on Survival - Sahin, Zekiye; Bayraktar, Burak; Karadeniz, Tugba; Sanci, Muzaffer (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: This study was conducted to evaluate the relationship of p53 and Ki67 expression with prognostic factors in patients who underwent surgery due to a diagnosis of endometrial cancer, and to evaluate their use as molecular markers that can help with survival prediction. STUDY DESIGN: This retrospective cohort study included patients who underwent surgery for endometrial cancer indication at the Gynecologic Oncology Clinic of the University of Health Sciences Tepecik Training and Research Hospital between 2011 and 2019, and whose p53 and Ki67 from the dissected material were pathologically studied and who underwent pelvic/paraaortic lymph dissection between the relevant dates. RESULTS: The study included 140 patients who met the inclusion criteria, 60% (n=84) of whom had endometrioid type endometrial carcinoma and 40% (n=56) had non-endometrioid type endometrial carcinoma. Estrogen and progesterone receptor positivity was significantly higher in the endometrioid type endometrial carcinoma group (p<0.001 and p<0.001, respectively). The non-endometrioid type endometrial carcinoma group had a high degree of positive staining (+3 and +4 staining) with p53 was 51.8%, while this rate was 11.9% in the endometrioid type endometrial carcinoma group. The non- endometrioid group also had a high degree of positive staining of Ki67 at 51.8%, whereas the endometrioid group had 25%. The total staining rate with p53 and Ki67 was significantly higher in the non-endometrioid type group (p<0.001 and p=0.001, respectively). The mean survival duration was less than six months in cases with high degree positive p53 [57.4±2.7, (52.1-62.8) vs 51.9±5.9, (41.8-61.9)] and the mean survival duration was less than eight months in cases with high degree positive Ki67 [59.6±2.9, (53.8-65.4) vs 51.6±4.3, (43.2-60.1)]. CONCLUSION: p53 and Ki67 can be new markers for the prediction of prognosis and duration in endometrial cancer. The results of this study pave the way for new studies: however, randomized controlled prospective and multi-center studies are needed for immunohistochemical measures to be used as a parameter.